SOURCE ROCK CHARACTERISTICS BASED ON GEOCHEMICAL ANALYSIS AND 1D BURIAL HISTORY MODELING IN THE “NAY” FIELD SOUTH SUMATRA BASIN - Yoza, Nizalia Azzahra; Butarbutar, Elrey Fernando; Sendjadja, Yoga Andriana; Ilmi, Nisa Nurul (Faculty of Geological Engineering, Universitas Padjadjaran, 2023)
The research is located in the